2021
DOI: 10.46542/pe.2021.211.373381
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing asynchronous video interview software for virtual pharmacy OSCEs during the COVID-19 pandemic

Abstract: Background: The COVID-19 pandemic required pharmacy educators to seek creative and innovative ways of delivering learning outcomes in the virtual environment. Objective Structured Clinical Examinations (OSCEs) have been particularly challenging to deliver online. Objective: To explore the use of asynchronous video interview software as a platform for virtual OSCEs in pharmacy education, and for conducting brief structured research interviews. Method: Fourth year Bachelor of Pharmacy students at an Australian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In contrast, while the Big Interview platform allowed for asynchronous virtual OSCEs to be undertaken during the pandemic, students observed that the one-sided nature of the consultations lost some of the real-world authenticity of live and synchronous patient interactions. It was recommended that in future learning and teaching, Big Interview might be better suited to junior pharmacy students, providing them an avenue to self-reflect on and self-correct their own patient communication skills safely [20]. This has since been adopted, and Big Interview now serves as the key platform for both formative and summative asynchronous OSCEs for first and second year pharmacy students enrolled in the Griffith University Bachelor of Pharmacy degree program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, while the Big Interview platform allowed for asynchronous virtual OSCEs to be undertaken during the pandemic, students observed that the one-sided nature of the consultations lost some of the real-world authenticity of live and synchronous patient interactions. It was recommended that in future learning and teaching, Big Interview might be better suited to junior pharmacy students, providing them an avenue to self-reflect on and self-correct their own patient communication skills safely [20]. This has since been adopted, and Big Interview now serves as the key platform for both formative and summative asynchronous OSCEs for first and second year pharmacy students enrolled in the Griffith University Bachelor of Pharmacy degree program.…”
Section: Discussionmentioning
confidence: 99%
“…The OSCEs could be recorded if necessary. Asynchronous OSCEs were also completed each day using the Big Interview platform [19], which was originally designed for asynchronous video interviews but repurposed in this context for virtual OSCEs [20]. Teams were provided with an access code for the daily cases.…”
Section: Stage 1: 2020 Virtual Deliverymentioning
confidence: 99%
See 1 more Smart Citation